Shaping Future Science Educators: Exploring First-Year Pre-Service Teachers’ Mastery of PISA-Style Challenges - Falentino, Charlos; Anggara Duta Medika; Evanita Mutang; Nuryadin, Atin; Efwinda, Shelly; Sulaeman, Nurul Fitriyah; Tanlianto, Alphero (LPPM STKIP Kusuma Negara, 2025)
This study investigates first-year science pre-service teachers’ abilities and perspectives on PISA questions, addressing Indonesia's low PISA rankings and challenges in teacher preparation. A total of 153 first-year students from four programs at Mulawarman University (mathematics, biology, physics, and computer education) participated. Using a mixed-methods approach, quantitative data were collected through validated PISA test instruments, while qualitative insights were drawn from open-ended responses. The results showed no significant differences in PISA scores by gender or study program, but significant differences emerged when comparing first-year students to third-year students and professional teachers, with first-year students scoring lower. Qualitative findings revealed themes such as the cognitive challenges posed by PISA questions, their ability to foster critical thinking, unfamiliarity with the format, and their real-world relevance. Despite difficulties, many participants found the questions engaging and valuable for developing analytical skills. These findings highlight the need to incorporate PISA-style assessments in teacher education programs to enhance higher-order thinking and better prepare pre-service teachers for international standards in education.